A new species of the snapping shrimp genus Alpheus (Crustacea: Decapoda: Caridea: Alpheidae) from Japan, associated with the innkeeper worm Ikedosoma elegans (Annelida: Echiura: Echiuridae) - Komai, Tomoyuki (Zootaxa, 2015)
A new species of the snapping shrimp genus Alpheus Fabricius, 1798, Alpheus ikedosoma, is described and illustrated on the basis of material from Boso Peninsula and Ariake Sea, Japan. All examined specimens were extracted with the help of a bait suction pump from burrows of innkeeper worm (Annelida: Echiura), constructed on easily accessible intertidal sand beaches or sand flats. The host worm from Boso Peninsula was identified as Ikedosoma elegans (Ikeda, 1904) (Echiuridae). The new species is tentatively referred to the A. brevirostris (Olivier, 1811) species group, but it is characteristic in having several unusual features for the group, such as the very short rostrum without dorsal ridge, the absence of adrostral grooves on the carapace, the strongly reduced dorsolateral spines on the telson, the unarmed antennal basicerite, the non-elongate, almost glabrous major chela, and the lack of movable spines or spinules on ventromesial margin of each cheliped merus. The new species represents the sixth species of Alpheus associated with echiuran burrows.